2018
DOI: 10.1021/acs.langmuir.8b01932
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Catalytic Activity of Oxo-Hydroxo Titanium Sub-Nanoislets Grafted on Organically Modified Mesoporous Silica

Abstract: The reaction between titanium alkoxides, [Ti­(OR)4], and surface silanol groups is widely used to generate grafted oxo-hydroxo titanium species, whose size is difficult to control. Partial capping of the surface silanols in the presence of the masking pattern of self-repelling tetramethylammonium ions allows us to isolate surface silanol islets, on which isolated titanium ions and dimeric oxo titanium species can be generated up to 2 Ti/Si mol %. Above this loading, and up to ∼8 Ti/Si mol %, higher oligomers (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…These “TS‐1‐(OOH) 2 ” sites enable the epoxidation of propylene with H 2 O 2 via an oxygen‐transfer transition state (Scheme 3d, 9 ) similar to the electrophilic epoxidation by peracids. In fact, anterior studies also suggested that high epoxidation activity does not imply that Ti oligomers should be absent from the catalyst [81–83] . Nevertheless, it is usually admitted that highly coordinated Ti species are less active and selective in epoxidation, [56] whereas pure TiO 2 typically shows no activity as it lacks free coordination sites.…”
Section: Strategies To Improve Ti‐based Heterogeneous Epoxidation Catalystsmentioning
confidence: 99%
“…These “TS‐1‐(OOH) 2 ” sites enable the epoxidation of propylene with H 2 O 2 via an oxygen‐transfer transition state (Scheme 3d, 9 ) similar to the electrophilic epoxidation by peracids. In fact, anterior studies also suggested that high epoxidation activity does not imply that Ti oligomers should be absent from the catalyst [81–83] . Nevertheless, it is usually admitted that highly coordinated Ti species are less active and selective in epoxidation, [56] whereas pure TiO 2 typically shows no activity as it lacks free coordination sites.…”
Section: Strategies To Improve Ti‐based Heterogeneous Epoxidation Catalystsmentioning
confidence: 99%
“…Fang et al reported the epoxidation of cyclohexene by oxo-hydroxo Ti IV species grafted on organically modified mesoporous silica of 3 nm pore diameter. [25] While very elegant, the elaboration of the heterogenous catalyst required a multi-step surface molecular engineering to install the Ti IV active species in the confined space of the templated porous silica. Additionally, this catalytic system was poorly active with hydrogen peroxide as oxidant and required the use of the less benign tert-butyl hydroperoxide instead.…”
Section: Resultsmentioning
confidence: 99%
“…This means that the travel of the reactants across the surface to the active site cannot be ignored. 12 Our goal is to isolate this travel step by sterically conning a reaction that follows the Langmuir-Hinshelwood pathway. By placing barriers at different distances, we hope to understand how much space a heterogeneous reaction needs in relation to the reactant's size.…”
Section: K ¼ a Ementioning
confidence: 99%